Can we extend the prolonged effects of a 180-s stretching exercise by applying an additional 15-s stretching bout? - Nakamura, Masatoshi; Kasahara, Kazuki; Murakami, Yuta; Takeuchi, Kosuke; Thomas, Ewan; Scardina, Antonino; Konrad, Andreas (Frontiers in Sports and Active Living, 2024)
Introducation This study aimed to clarify whether or not the prolonged effect of a 180-s static stretching (SS) exercise could be maintained for a longer period by performing an additional short-term (15-s) SS exercise following a 15-min rest. Methods The participants were 15 healthy untrained adult males in three conditions: (1) SS condition (180-s SS exercise only); (2) SS + 15 s condition (180-s SS and 15-s SS exercise during the rest period); and (3) noSS + 15-s condition (15-s SS exercise only). The knee flexion range of motion (ROM), pain pressure threshold (PPT), and tissue hardness were measured before (PRE), immediately after (POST), and 15 min and 30 min after the SS exercise. Results and discussion Significant interaction effects were observed in all variables. Post hoc tests showed that knee flexion ROM showed an immediate significant change (P < 0.05) and also at 15 min and 30 min after the SS exercise in the SS + 15 s condition. Tissue hardness showed an immediate significant decrease (P < 0.05) and also at 15 min, but not at 30 min after the SS exercise in the SS + 15 s condition. The additional short-term (15 s) SS exercise in the rest period may have a potential long-lasting effect on ROM increase and tissue hardness decrease.